Prevalence of Periodontal Disease and Caries Associated with Erupted Third Mandibular Molar - Farhan Javed, Nighat Shafi, Tabassum Awais, Maryam Virda, Madiha Maryam, Sana Chaudhry, Sadia Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the prevalence of periodontal disease and caries on 2nd mandibular molar in association with erupted 3rd molars. Methodology:: This cross sectional study was conducted at the Periodontology Department, Avicenna dental college, Lahore from July 2021 to June 2022. A total of 81 patients were examined in the age range of 21-50 years. Patients of both genders were assessed. Data was entered and analysed by IBM SPSS 25. Level of significance was kept at p-value ≤ 0.05 Results: Total of 81 patients were examined with the total number of teeth evaluated were 156. Age taken as demographic variable was further divided into three groups. Group 1 consisted of patients between the age range of 21-30 years n=18 (22.22%). Group 2 have patients between the age range of 31-40 years n=43 (53.09%) and Group 3 consisted of age range of 41-50 years patients n=20 (24.69%).Highest prevalence of distal caries was related to level A (68.33%) and periodontal disease was prevalent in level C followed by level B molars Conclusion: Regardless of eruption status, 3rd molar is associated with occurrence of periodontal disease and caries on 2nd mandibular molars. Ergo, regular clinical evaluations and monitoring are required even in apparently symptom free 3rd mandibular molars, as their existence is analogous to Distal Surface Caries (DSC) and PPD≥5mm development in mandibular 2nd molars. Else, to improve the long term survival of 2nd mandibular molars, prophylactic extraction of 3rd mandibular molars can be considered as a treatment option. Keywords: Eruption status, distal surface caries, periodontal disease.